VITAL CONCERNS IN CURRICULUM DEVELOPMENT IN SCIENCE AND MATHEMATICS - Kulkarni, V.G. (SCHOOL SCIENCE, 2013)
During the past three decades or so, India has been struggling hard to achieve universalisation of elementary education. While considerable progress has been achieved in terms of creating an infrastructure, that is, in terms of providing a school within walking distance and in terms of ensuring that there is at least one teacher available per school, the target of achieving universalisation has been eluding us all the time. The aims of achieving 100 per cent literacy, of ensuring 100 per cent enrolment in Class I, and of retaining all the enrolled pupils for at least four or five years, all seem hopelessly beyond realisation. At this juncture when we are passionately discussing the new policy on education, and when for the first time in our history we have acquired powerful technologies like satellite communication and home computers, it would be very relevant and meaningful to discuss the new concerns in curriculum development in science and mathematics, in terms of the explicitly declared national goals and objectives. The brief note aims at listing some of these concerns with the hope that these will be reflected in curriculum development